Every breath you take. Every freight you make: Environmental pollution index for road transportation - CEZARINO, LUCIANA ORANGES; BAESSE, LORENA; FILHO, ADHEMAR RONQUIM; FREITAS, MARLOS ROCHA (Brazilian Journal of Operations & Production Management, 2021)
Goal: This study analyzes the impacts of the transportation sector on air pollution within the scope of one major Brazilian metropolitan region. Design/Methodology/Approach: A literature review was conducted on the subject’s constructs, with subsequent reasoning grounded on the fleet’s characteristics and data obtained from in-depth interviews from a government transportation agency. Results: The results show Brazil’s contextual evidence that risk management for the haulage sector should consider air pollution’s negative impacts. With air quality standards as an essential reference, it is possible to observe that the city of Uberlândia does not effectively manage air quality. Limitations of investigation: One limitation of this research is related to the representativeness of the sample. The research also recommends future studies to use government policies for the improvement of the framework. Practical implications: The local and contextual addressing of air pollution and transport correlation in one focal point for cargo transportation at a national level pontentially contributes to environmental public policies. Originality/value: Originality value resides in considering emissions from cargo vehicles as a significant factor in this process of air pollution in a specific context of a metropolitan area of an emerging economy that has its transportation modal grounded on trucking freight.